2015
DOI: 10.1016/j.jpowsour.2015.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Effective diffusivity in partially-saturated carbon-fiber gas diffusion layers: Effect of local saturation and application to macroscopic continuum models

Abstract: Macroscopic continuum models are an essential tool to understand the complex transport phenomena that take place in gas diffusion layers (GDLs) used in polymer electrolyte fuel cells (PEFCs). Previous work has shown that macroscopic models require effective properties obtained under uniform saturation conditions to get a consistent physical formulation. This issue, mostly unappreciated in the open literature, is addressed in detail in this work. To this end, lattice Boltzmann simulations were performed on tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 68 publications
4
112
1
Order By: Relevance
“…In fact, our results for the SGL material are also close to the trend line described with e 2.5 . However, in contrast to the pronounced ip-tp anisotropy reported by Garcia-Salaberri for Toray [32,33], the anisotropy of our SGL material is much smaller.…”
Section: Validation Of Predicted Diffusivity and Comparison With Convcontrasting
confidence: 94%
See 3 more Smart Citations
“…In fact, our results for the SGL material are also close to the trend line described with e 2.5 . However, in contrast to the pronounced ip-tp anisotropy reported by Garcia-Salaberri for Toray [32,33], the anisotropy of our SGL material is much smaller.…”
Section: Validation Of Predicted Diffusivity and Comparison With Convcontrasting
confidence: 94%
“…But also with the T-S model the effective diffusivity of our GDL (SGL 25BA) is overestimated, which is compatible with the findings reported by Zamel and Li [5]. In recent studies by Garcia-Salaberri et al [32,33] it was shown that the gas diffusivity in GDL (Toray) follows the trends described by e 2.5 for ip and e 3.5 for tp directions. In fact, our results for the SGL material are also close to the trend line described with e 2.5 .…”
Section: Validation Of Predicted Diffusivity and Comparison With Convsupporting
confidence: 91%
See 2 more Smart Citations
“…The SNOW algorithm was applied to an image of Toray 120 with no PTFE, used in previous studies [55,56]. This material has a porosity of 75% [57], a thickness of 360 microns, fiber diameter around 10 microns, and a permeability coefficient tensor [58] …”
Section: Fibrous Mediamentioning
confidence: 99%